1968
DOI: 10.1073/pnas.60.1.300
|View full text |Cite
|
Sign up to set email alerts
|

"Contact inhibition" of cell division in 3T3 cells.

Abstract: The 3T3 cell, an established line of mouse fibroblast cell, has been considered to be extremely sensitive to "contact inhibition" of cell division. Under the usual culture conditions, 3T3 cells grow rapidly in sparse culture, but cell division stops after the cells become confluent, at approximately 106 cells per 6-cm dish. The cell monolayer has a typical "cobblestone" appearance. Todaro, Lazar, and Green1 have described studies of the effect of serum on cell division in these "contact-inhibited" cells. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
150
0
2

Year Published

1974
1974
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(160 citation statements)
references
References 3 publications
8
150
0
2
Order By: Relevance
“…4. On the basis of this experiment, we suspect that contact inhibition is not a mechanism of growth control but rather reflects the depletion of growth factors from serum, as suggested by Holley and Kiernan (7).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…4. On the basis of this experiment, we suspect that contact inhibition is not a mechanism of growth control but rather reflects the depletion of growth factors from serum, as suggested by Holley and Kiernan (7).…”
Section: Discussionmentioning
confidence: 78%
“…cessation of growth at confluency may reflect a transition from a proliferative stage to a resting stage, under very strict control of serum growth factors (7). It has been observed that when 3T3 cells are maintained in 30% serum with a change of fluid daily, contact inhibition is not seen; the cells grow to a very high density (7).…”
Section: Discussionmentioning
confidence: 97%
“…Without rinsing, the cells were fixed with 2 ml per plate of cold 5% trichloroacetic acid (TCA) and incubated at 40 for an hour. Then the TCA suspensions were transferred to a cold centrifuge tube, pooled with a 5% TCA wash of the plates, and pelleted at 10,000 rpm for 5 (Table 2). However, the lines A-ySV4 and AySV5, which were selected for their inability to grow in 10% agamma-depleted calf serum (7), retained the low cAMP level of SV3T3101 ( (Table 3).…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that one factor responsible for the cessation of growth of contact-inhibited cells is the depletion of growth factors in the medium, especially serum growth factors (5,6). If contact inhibition in the BrdU-dependent cells in the absence of BrdU is due to such depletion of growth factors, then BrdU seems to alter the cells in such a way that these factors are no longer required.…”
Section: Discussionmentioning
confidence: 99%